Influence of Gonadotrophin‐Induced First Oestrus on Gilt Fertility. Issue 6 (14th August 2014) - Hidalgo, DM; Friendship, RM; Greiner, L; Manjarín, R; Amezcua, MR; Domínguez, JC; Kirkwood, RN
Contents The aim of this study was to determine the association between the oestrous response of pre‐pubertal gilts to gonadotrophin injection or boar exposure and their subsequent farrowing rate and litter size. At 154 days of age, randomly selected pre‐pubertal gilts received an intramuscular injection of 400 IU equine chorionic gonadotrophin plus 200 IU human chorionic gonadotrophin (PG600®; Merck Animal Health; n = 181). From the remaining pool of animals not treated with hormones, the first gilts showing signs of oestrus were selected to act as controls (n = 201). Boar exposure began at 155 days of age for both groups, and gilts were bred at a weight of approximately 130 kg. Comparisons were made between PG600®‐treated gilts exhibiting oestrus or not within 7 days post‐injection (early and late responders, respectively) and control gilts exhibiting oestrus or not within 30 days after beginning of boar exposure (select and non‐select control gilts, respectively). By 162 days, oestrus was detected in 67.5% of PG600®‐treated gilts compared with 5.7% of control gilts (p < 0.0001). The proportion of animals observed in oestrus at least three times before breeding was greater for select control gilts compared with early and late responder PG600®‐treated gilts (p ≤ 0.001). There were no significant differences in farrowing rate and litter size between the four treatment groups. These data indicate that PG600® is an effective tool to induce an earlier oestrus in gilts, that subsequent farrowing rate and born alive litter size compare favourably to that of select gilts and that gilts failing to respond promptly to hormonal stimulation do not exhibit compromised fertility.